Content-based image retrieval system - Ba, Li (2008)
With tremendous growth in the numbers and sizes of digital image and video collections, it is very necessary to develop effective and efficient tools to index and search these multimedia information. Techniques of Content-Based Image Retrieval (CBIR) are presented to conduct similarity queries in image databases, which are based on some visual features of images, such as color, texture, shape, and regions. Our work attempted to investigate some issues in CBIR and develop an effective and efficient image Database Management System (DBMS). Some important issues in CBIR were discussed, such as feature extraction, similarity measures, indexing structures, and system effectiveness evaluation. To know about contemporary CBIR systems, some notable CBIR systems were reviewed and compared.